On the ρ-Interpolative Ćirić–Reich–Rus-Type Fixed-Point Theorems - Müzeyyen Sangurlu Sezen; Serap Özcan; Manuel De la Sen; Sina Etemad; Raaid Alubady (Journal of Mathematics)
In this study, we aim to introduce some new definitions called ρ-interpolative Ćirić–Reich–Rus-type and Kannan-type fuzzy contractions by using the concepts of ρ-admissibility (by Dinarvand (2017)) and ς-comparison function (by Mihet (2008)). We prove some fixed-point theorems for ρ-interpolative Ćirić–Reich–Rus-type and Kannan-type fuzzy contractions in M-complete fuzzy metric spaces. We presented some of the results established in fuzzy metric spaces to the partially ordered fuzzy metric spaces. Some examples support the results obtained in this manuscript. As an application, we present the existence of a solution to the entity uniqueness problems.